2022
DOI: 10.3390/v14091949
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Molecular Characterization of the Lytic Bacteriophage SoKa against Pseudomonas syringae pv. syringae, Causal Agent of Citrus Blast and Black Pit in Tunisia

Abstract: Pseudomonas syringae pv. syringae (Pss), the causal agent of citrus blast and black pit lesion of lemon fruit, continues to cause serious damage in citrus production in Tunisia. Faced with the rapid emergence of the disease and the inefficiency of conventional control methods, an alternative strategy based on the use of bacteriophages was pursued in this study. The lytic Pss bacteriophage SoKa was isolated from soil collected from Tunisian citrus orchards. Analysis of the host range showed that SoKa was able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Among the growth properties, the MOI (refers to the ratio of the number of phages applied to the target pathogen) value is indeed a critical factor in the use of phages as biopesticides. In this study, the MOI value for P. syringae TE phage is found 0.1, which is encountered in the range of 0.1–10 in the literature (Akbaba & Ozaktan, 2021; Oueslati et al., 2022; Pinheiro et al., 2019). A low MOI value implies that there are fewer phages than target pathogens in the culture, decreasing the cost‐effectiveness of phage biopesticide applications in agriculture (Holtappels et al., 2021; Svircev et al., 2018).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Among the growth properties, the MOI (refers to the ratio of the number of phages applied to the target pathogen) value is indeed a critical factor in the use of phages as biopesticides. In this study, the MOI value for P. syringae TE phage is found 0.1, which is encountered in the range of 0.1–10 in the literature (Akbaba & Ozaktan, 2021; Oueslati et al., 2022; Pinheiro et al., 2019). A low MOI value implies that there are fewer phages than target pathogens in the culture, decreasing the cost‐effectiveness of phage biopesticide applications in agriculture (Holtappels et al., 2021; Svircev et al., 2018).…”
Section: Discussionsupporting
confidence: 56%
“…While phage studies targeting P. syringae pv. syringae caused bacterial canker are documented in the scientific literature (Akbaba & Ozaktan, 2021; Oueslati et al., 2022; Pinheiro et al., 2019) it is important to acknowledge that diverse ecological conditions, including altitude, temperature, soil type, oxygen levels, microflora, macroflora and so on can lead to variations in species or subspecies diversity. These variations can result in differences in genomic, metabolic and phenotypic traits among related species.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the phages adsorbed to lipopolysaccharide residues on the Psa cell surface both in vitro and in planta, and significantly reduced the bacterial load in planta . Our immature pear assay demonstrated a similarly significant effect of disease mitigation after administering phages, comparable to Pss phage SoKa in citrus ( 5 ). Our study further emphasizes the ability of phages to be used as biocontrol agents to reduce the effects of disease in crops as comprehensively reviewed elsewhere ( 57 , 58 )…”
Section: Discussionmentioning
confidence: 60%
“…Among them, Pseudomonas syringae pv. syringae (Pss) is considered one of the most generalists due to its ability to infect upward of 180 plant species ( 3 ), including multiple Prunus species, as well as other stone fruits, mango, citrus, and pear ( 4 6 ). Multiple Pss strains have been found to be pesticide resistant over a wide variety of chemical control measures, especially copper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation